MINERALOGY AND CRYSTAL STRUCTURE OF BOUAZZERITE FROM BOU AZZER, ANTI-ATLAS, MOROCCO: Bi-As-Fe NANOCLUSTERS CONTAINING Fe3+ IN TRIGONAL PRISMATIC COORDINATION - Brugger J.; Meisser N.; Krivovichev S.; Armbruster T.; Favreau G. (My University, 2007)
Bouazzerite, Bi6(Mg,CO)11, Fe14 [AsO4]18O12 (OH)4 (H2O)86, is a new mineral occurring in "Filon 7" at the Bou Azzer mine, Anti-Atlas, Morocco. Bouazzerite is associated with quartz, chalcopyrite, native gold, erythrite, talmessite/ roselite-beta, Cr-bearing yukonite, alumopharmacosiderite, powellite, and a blue-green earthy copper arsenate related to geminite. The mineral results from the weathering of a Vaiscan hydrothermal As-Co-Ni-Ag-Au vein. The Bou Azzer mine and the similarly named district have produced many outstanding mineral specimens, including the world's best erythrite and roselite. Bouazzerite forms monoclinic prismatic {021} crystals up to 0.5 mm in length. It has a pale apple green color, a colorless streak, and is translucent with adamantine luster. dcalc is 2.81(2) g/cm3 (from X-ray structure refinement). The new mineral is biaxial with very weak pleochroism from yellow to pale yellow; the refractive indices measured on the (021) cleavage face range from nmin = 1.657 to nmax = 1.660; the Gladstone-Dale relationship provides a value of 1.65. The empirical chemical formula is Bi6.14 Fe12.6 Mg8.45 Co0.48 Ni0.12Ca0.23 (AS17. 0Cr0.64 Si0.32)∑=18.0 O174.6 H184. Bouazzerite is monoclinic, P21/n, Z = 2, with a = 13.6322(13) Å, b = 30.469(3) Å, c = 18.4671(18) Å, β = 91.134(2)°, and V = 7669.0(13) Å 3. The eight strongest lines in the X-ray powder diffraction pattern are [d in Å β = 91.134(2)°, and V= 11.79(100)(021̄), 10.98(80)(101/1̄01),10.16(80) (1̄20),7.900(80)(022), 12.45(70) (11̄0),15.78(60) (01̄1), 3.414(40)(333/400), 3.153(40) (353̄/22̄5). The crystal structure of bouazzerite is based upon [Bi3Fe7O6 (OH)2 (AsO4)9]11- anionic nanoclusters that are built around [trigonalprimasticFe33+(OH) O12]2]29_ groups, containing one Fe3+ ion in trigonal prismatic coordination and six Fe3+ ions in octahedral coordination. The nanoclusters have a diameter of about 1.3 mn and are linked together by chains of Mg(O,H2O)6 octahedra. The resulting arrangement displays channels down [100] that contain structural water. Bouazzerite is the first mineral based upon Bi- and As-containing ferric nanoclusters. Its discovery provides a unique insight into transport mechanisms of toxic elements in the oxidation zones of sulfide mineral deposits in the form of complex Fe-As nanoparticles.
Keywords: ANTI-ATLAS; BOU AZZER PROVINCE; BOUAZZERITE; CRYSTAL STRUCTURE DETERMINATION; MOROCCO; NEW MINERAL; TRIGONAL PRISMATIC COORDINATION